Subclinical hypercortisolemia – a therapeutic dilemma - Agata Tuszyńska; Lucyna Bednarek-Papierska (Wiedza Medyczna, 2023)
Subclinical hypercortisolemia is the most common secretory function disorder of the adrenal glands caused by the presence of adenoma or hyperplasia of the adrenal cortex.  The primary hormonal test performed in the diagnosis of an incidentaloma is a test with 1 mg of dexamethasone. Lack of cortisol suppression after taking 1 mg of dexamethasone is a screening test for hypercortisolemia. Depending on the clinical symptoms, we are able to distinguish between overt and subclinical forms of cortisol excess. Subclinical hypercortisolemia does not cause somatic features of Cushing's syndrome.However, even a slight excess of cortisol has been found to significantly increases cardiovascular risk, prevalence of osteoporosis with vertebral fractures and impairs glucose tolerance. In patients with subclinical hypercortisolemia, there are no determined criteria to define strict indications for adrenalectomy. There are many studies showing the beneficial effect of resection of the adrenal adenoma producing cortisol, which led to a reduction in blood pressure and an improvement in the metabolic profile in patients. However, these positive changes do not apply to all patients. As a result, the current European recommendations refer to surgical treatment only when pharmacological treatment fails to achieve good control of hypertension, glucose metabolism or weight reduction.Some authors believe that not only the adrenal gland tumor may be a cause of the metabolic syndrome, but on the other hand, the hyperinsulinism causes adrenal hyperplasia and excessive secretion of cortisol. In every clinical case, the surgery indication should be carefully analyzed. Primary management is the implementation of pharmacological treatment, regular physical activity and an appropriate diet.